2020
DOI: 10.1097/gox.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

Transfeminine Gender Confirmation Surgery with Penile Inversion Vaginoplasty: An Initial Experience

Abstract: Background: To detail the early experience with and results of a transfeminine (TF) genital reconstruction at an established plastic surgery practice in Western New York. Methods: Between June 2016 and June 2019, 30 patients underwent penile inversion vaginoplasty for TF gender reassignment. All patients fulfilled World Professional Association for Transgender Health and NY State criteria for reassignment surgery. All surgeries were carried out at a large, government-owned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…As such, some patients may not report (or recognize) loss of vaginal depth. Despite this, Loree et al 25 reported that in their initial experience of 30 patients, vaginal deepening was the main reason for revision surgery. Furthermore, Schardein, Zhao & Nikolavsky reported that 5% of their reoperations were for augmentation of vaginal depth 32 …”
Section: Complications Following Vaginoplastymentioning
confidence: 99%
See 4 more Smart Citations
“…As such, some patients may not report (or recognize) loss of vaginal depth. Despite this, Loree et al 25 reported that in their initial experience of 30 patients, vaginal deepening was the main reason for revision surgery. Furthermore, Schardein, Zhao & Nikolavsky reported that 5% of their reoperations were for augmentation of vaginal depth 32 …”
Section: Complications Following Vaginoplastymentioning
confidence: 99%
“…19,20,23,25,27,30,31 The decrease in incidence has been attributed to a change of surgical technique, 17,23,25 such as spatulation of the urethral meatus, 17,23 "simple anastomosis [of the urethral meatus] to [the] external genitalia" (presumably referring to a less ischemic suture), 17 and minimal manipulation of the internal anatomy of the urethra. 25 Rossi et al 28 hypothesized that scar formation and decreased local vascularity were contributory factors in all their cases of meatal stenosis. In addition, some authors postulate that Foley catheters that are removed too early (defined by some authors as before post-operative day five) or too late (defined by some authors as after post-operative day five) may contribute to meatal stenosis.…”
Section: Reprodumentioning
confidence: 99%
See 3 more Smart Citations